Penerapan Metode Simple Multi Attribute Rating Technique (SMART) Dalam Penerimaan Karyawan Baru - Lidya Puspita Dewi (SNASTIKOM, 2023)
Recruitment of new employees is an activity carried out by a company to recruit new members that the company needs to fill certain positions or positions that are needed. The process that runs in the company is subjective, which results in the process not being in accordance with needs, and employees who pass the selection are not competent in their field of work, so there are still obstacles in accepting new employees. As a result, companies need to implement appropriate systems to assist in recruiting new employees. To overcome this problem, it is recommended that new employee recruitment data be processed using a Decision Support System (DSS) using the simple multi attribute rating technique (SMART) method. The simple multi attribute rating technique method is that each alternative consists of criteria, each of which has a value and weight that shows how important it is in relation to the other criteria. The purpose of this research is to support the analysis process of employee acceptance values and support employee acceptance in making decisions based on the required criteria. Angga Retsa Darma, the first alternative, obtained the highest score after data processing using the SMART method, with a value of 0.700 which indicates a higher probability of being accepted for work. Muhammad Reza, the fourth alternative, received the lowest score with a value of 0.450, indicating the smallest chance of being accepted.